Antifungal, cytotoxic and chemical analyses of essential oils of Lippia origanoides H.B.K grown in Colombia (2011)
ABSTRACT: Introduction: Aspergillus fumigatus is most commonly associated to invasive aspergillosis. Strong antifungal activity against A. fumigatus of L. origanoides essential oil gives a new added value to this natural product from Boyacá-Colombia. Aims: The increase in fungal infections, the development of resistance and toxicity of wide-spectrum antifungals have led to a constant search for therapeutic alternatives. The chemical composition, antifungal and cytotoxic activity of nine essential oils obtained from L. origanoides were evaluated and the relationship between the antifungal activities of the oil and of its major components were explored. Methods and Results: Antifungal activity was determined following the protocols AFST-EUCAST for Candida krusei and C. parapsilosis, and CLSI-M38A for Aspergillus fumigatus and A. flavus. The GC-MS analysis identified three chemotypes: thymol, carvacrol and p-cymene/trans-beta-caryophyllene. The essential oil of the thymol chemotype was the most active in antifungal assays with MIC values of 157.5, 198.4, 125 and 31 μg ml-1 against C. parapsilosis, C. krusei, A. flavus and A. fumigatus, respectively. The major components carvacrol and thymol were not active against A. fumigatus at concentrations below 157.5 μg ml-1. In general, the oils were not cytotoxic. Conclusions: The essential oil of the thymol chemotype of L. origanoides from the region of Boyacá- Colombia showed the highest antifungal activity against A. fumigatus among all the oils and major components tested.